Propofol Causes Consciousness Loss by Affecting GABA-A Receptor in the Nucleus Basalis of Rats - Yunlong Xing; Kai Li; Yuan Jiao; Zinan Li (Behavioural Neurology)
Objective. Propofol is a classical anesthetic and induces consciousness loss, and gamma-aminobutyric-acid-type-A (GABA-A) receptor is its target. Righting reflex is associated with conscious response. The nucleus basalis (NB) acts as a major relay between the reticular activating system and the frontal cortex (FC). Propofol may mediate righting reflex by affecting GABA-A receptor in NB. Methods. Fifty male SD rats (250-350 g) were divided into parts I and II. In part I, 20 male SD rats were randomly divided into control group (CG) and NB-lesion group (NG, ibotenic acid-induced NB lesion). In part II, 30 male SD rats were treated with saline (0.9% NaCl, SG group), muscimol (a GABA-A receptor agonist, MG group), and gabazine (a GABA-A receptor antagonist, GG group) in NB, respectively. Two weeks later, the activity of the rats was measured between CG and NG groups. The rats were intravenously injected with propofol (50 mg/kg/h) to test the time of loss of righting reflex (LORR) in all rats. When LORR occurred, the rats received single administration of propofol (12 mg/kg) to measure the time of return of righting reflex (RORR). Electroencephalogram (EEG) activity of the frontal cortex (FC) was recorded. Results. The numbers of NB neurons were reduced by 44% in the NG group compared to the CG group (p<0.05) whereas the activity of rats was reduced a little in the NG group when compared with the CG group, but the statistical difference was insignificant (p>0.05). The dose-response curve of propofol shifted to the left in the NG group, and the statistical difference for the time of LORR was insignificant between the two groups (p>0.05). However, the time of RORR and FC delta power increased in the NG group compared with the CG group (p<0.05). In part II, the time of RORR and FC powder increased in the MG group when compared to the SG group while reverse results were observed in the GG group (p<0.05). There was no significant influence on the time of LORR and ED50 among the three groups (p>0.05). Conclusions. The unilateral NB lesion increased the recovery time and FC delta power, and the NB region might be involved in the emergence after propofol administration. Propofol plays a crucial role for causing conscious loss by affecting GABA-A receptor in NB.